The determination of energy costs during soccer matches: Comparative analysis between measured and calculated energy expenditure - Venzke, J.; Nardiello, D.; Platen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The metabolic demands of soccer and other team sport players have been a subject of research for many years. However, there is no method for estimating the energy costs (EC) during official matches. A new mathematical approach1 can be used to calculate metabolic loads during a match. Using this method it might be possible to determine EC from velocity and acceleration data measured by global positioning system (GPS) or comparable technology. The aim of the study was to validate the new mathematical approach for the determination of metabolic demands by comparing the results of the mathematical analysis against the direct measurement with spirometry (SM) during a soccer match. Methods: 22 healthy soccer players from the 5th German League agreed to participate in a simulated soccer match with a playing time of 90 min and a regular halftime break (15 min). 8 of the subjects (24.4±2.1 y, 183.3±6.9 cm, 82.6±8.0 kg) wore a portable GPS system (GPI-Sports, 5 Hz) for the determination of accelerations and decelerations and velocities, and additionally a portable SM system. GPS and SM data were recorded simultaneously to compare direct vs. indirect determination of EC. The match was separated into four quarters to acquire an accurate analysis. Data was analyzed by means of a paired t-test and Pearsons chi-squared test. Results: EC determined by the mathematical approach underestimated directly determined EC by approximately 25% and was significantly lower compared to the directly determined EC (1030±287 vs. 779±171 kcal, 2p<0.05 for directly measured and calculated EC, respectively). The correlation between the calculated and directly measured EC was highly significant for the total game (R=0.88), the two halves (R1st =0.85, R2nd =0.96), and the last two quarters (R3rd =0.97, R4th =0.91) (2p <0.01). Discussion: Data showed that the determination of EC of a soccer match based on acceleration and velocity data using a new mathematical approach seems to be possible and valid however the results still underestimate the real energy costs. Correction factors are required for an even better approximation to the real EC, including corrections for movements with the ball, passing the ball, shots, jumps, and taking into account different ground conditions. Further studies will result in nearly exact estimation of EC of soccer matches and will help to optimize training loads.